Building an inclusive social protection system in South Africa - Fall, Falilou (OECD Publishing, 2020)
South Africa has an incomplete social protection system without a mandatory pension savings scheme. Designing a universal insurance pension system would allow to reduce the important government funded pension grant system and ensure that the old-age population has decent income. Only 40% of employees are contributing to a form of saving-retirement scheme, with often a low pension. Moreover, South Africa has a dual, public and private, health care system. Half of the country's health-care spending goes to the private sector, which covers only 16% of the population. Moreover, the health care system fails to deliver affordable quality services. The COVID-19 pandemic has highlighted the unequal distribution of health care services between public and private health providers. Around 70% of critical care beds available were in the private health care sector. Finally, the sizeable unconditional cash transfer system though reaching a large share of the population fail to lift many children in the poorest families above the poverty line
Keywords: Economics; South Africa